Evaluation Indicators and Development Strategies of Agricultural Revitalization for Rural Rejuvenation - Huang, Biing-Wen; Yang, Yu-Chen (Journal of Reviews on Global Economics, 2018)
The goal of rural rejuvenation is to establish newly regenerated rural villages via economic development and beautification. However, it is necessary to engage agriculture in rural areas as a basis to reach the goal. In order to effectively promote agricultural development, the objective of this study is to develop the related indicators as evaluation criteria. A modified Delphi method is applied to develop the questionnaire. The indicators are divided into two categories: requirement and implementation evaluation indicators. This implies indicators in both sides should be considered simultaneously for effectively promoting agricultural development. There are four dimensions, consisting of twelve items, which are included in requirement indicators. The four dimensions are to (1) activate agricultural production (2) to promote agricultural marketing (3) to construct the distinguishing features of rural life and culture, and(4) to develop leisure agriculture and rural village experiences. The implementation indicators are comprised of five dimensions including 21 items. The five dimensions are (1) community factors (2) human resource factors (3) local resource surveys (4) environmental and facilities planning, and (5) government subsidies and guidance. To determine the relative importance sequence of the target evaluation indicators, the fuzzy analytic hierarchy process (FAHP) is applied to calculate the weight for each item. Then, the quality function development method (QFD) is adopted to explore the relative importance sequence of implementing indicators. Based upon the important items of evaluation indicators, this study proposes the development strategies recommended for the agricultural authority.